Korespondencja - Biblioteka Narodowa.Instytut Bibliograficzny (1954)
Listy od następujących: Hiszpańska-Neumann, Maria 1954-1972 (32) k. 1-55. - Hleb-Koszańska, Helena (Instytut Bibliograficzny BN) 1965 (1) k. 56.
Mf 11059